The Impact of SDG12 on the Productivity of Firms and Consumption of Households - Alleah Samporna; Julius Patrick I. Buenabajo; Ma. Ella R Perez; Marie Antoinette L. Rosete (UJoST- Universal Journal of Science and Technology, 2022)
Responsible Production and Consumption have had considerable roles in sustainable development and how it affects economic growth for the countries. Moreover, inefficient consumption patterns of businesses lead to significantly large amounts of waste and excessive use of scarce natural resources. Meanwhile, irresponsible production may cause environmental degradation, resource shortages, and health risks. This article outlines the fundamental characteristics of sustainable consumption and production in achieving the Sustainable Development Agenda target of "Responsible consumption and production." Furthermore, this will present a comprehensive review of the literature on the Impacts of SDG 12 in promoting sustainable business practices, reducing food loss, and reducing environmental damage to preserve scarce natural resources. This research used a cross-sectional study coupled with simple linear regression and multiple regression analysis to measure the three indicators of SDG12 in Asian countries.